Enhancing Vocabulary Acquisition and Language Learning Through Corpus Linguistic Approaches: The Role of Onomastics in Teaching Batik Madura’s Cultural Identity - Siswanto, Wahyudi (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
Research on corpus linguistics in language learning has primarily emphasized lexical patterns, collocations, and discourse structures, yet their application to onomastics remains underexplored. Research on Batik Madura’s naming conventions has largely been descriptive, lacking integration into vocabulary acquisition and cultural identity development in English as a Foreign Language (EFL) instruction. To address this gap, this study examines the impact of corpus-based onomastic analysis on students’ vocabulary acquisition and cultural awareness. A sequential mixed-methods approach was employed, involving pre- and post-tests and a closed-ended questionnaire to measure lexical retention, semantic comprehension, and cultural identity awareness among 53 undergraduate students at STKIP PGRI Sumenep, Indonesia. Additionally, structured interviews with six selected students provided in-depth insights into their experiences with corpus-based learning. The findings revealed that exposure to Batik Madura’s naming conventions through corpus analysis improved students’ ability to recognize word formations and contextual meanings, leading to a deeper understanding of linguistic structures. However, some students encountered difficulties interpreting abstract cultural meanings embedded in names. The study suggests incorporating explicit instructional scaffolding to bridge conceptual gaps. These findings highlight the potential of onomastics-based corpus analysis in enhancing vocabulary learning while underscoring the need for pedagogical adjustments to optimize its effectiveness in EFL contexts.